Problème de contact avec mémoire longue et usure - Amanallah, Soumeia (University of Eloued جامعة الوادي, 2018)
في هذه المذكرة درسنا وجود ووحدانية الحل لمسألة حدية في ميدان الضغطية الكهربائية,وهي مسألة تواصل بين جسم كهرو-لزج- مرن ذو ذاكرة طويلة بتلف معين للجسم مع قاعدة متحركة. استعملنا صيغةڨرين للحصول على المسألة التغايرية ثم برهنا عن وجود ووحدانية الحل بالحجج التالية: متراجحة تغايرية ناقصية, معادلة In thisthesis, westudied the existence and uniqueness of the solution ofboundarycontact problem in piezoelectricity. Itis a contact problembetweenan electro-visco- elastic body with long memory and wear and a mobile base. Weused theGreen's formula for obtain the variational formulation of the problem and weproved the existence and uniqueness of the solution by the following arguments: ellipticvariationalinequation, differentialequation and fixed point
memoire master Mathématiques
Keywords: متراجحة تغايرية ناقصية, معادلة تفاضلية, نقطة ثابتة.; : Solar Tracker, Photovoltaics, Solar Energy, Arduino